Students’ Science Process Skill in Volcanoes Eruption Disaster Preparedness and Mitigation - Tyas, Rizki Arumning; Pujianto, Pujianto; Suyanta, Suyanta (Universitas Negeri Malang, 2021)
This study aimed to determine the achievement of the mastery of science process skills of students who are trained in integrated learning disaster risk reduction efforts. This research is an experimental research design with one sample control group design. The sample in this study were 60 students of 7th grade student in SMP N 2 Cangkringan, Yogyakarta, Indonesia. SMP N 2 Cangkringan is located near Merapi Mountain areas. Science process skills data were obtained using a process skills observation sheet that was filled in by the observer. Data analysis was performed descriptively. The results shows that the scientific process skills profile of students who were trained together with the training of volcanic eruption disaster mitigation increased at each meeting. The most significant improvement was observing, followed by predicting skills, communicating skills, and drawing conclusions